Theoretical explanation of the relationship between intention and organizational performance from the perspective of Islam. - Asadullah َAhmadi; Abdullah Tavakkoli; Ali Aqapirooz (اخلاق وحیانی)
AbstractDue to the importance of intention in the value of individual and organizational behaviors and practices from the Islamic point of view, which is emphasized in religious sources, this study aims to theoretically examine the relationship between intention and organizational performance from the perspective of Islam and with the aim of analyzing and explaining the effect of intention on value. Organizational performance is based on religious sources (verses and hadiths). In this research, the library method has been used for data collection and the method of thematic interpretation and documentary analysis has been used for the analysis of data in the holy verses section of the Holy Quran and Mr. Masoudi's three-stage hadith research method has been used in the narrations section. Finally, by explaining the conditions of correct intention from the perspective of Islam, the research has reached the conclusion that the effect of intention on organizational performance is the product of intentional influence on the two axes of action and the result of action. Have good deeds and good intentions.